Aplikasi Sistem Informasi Simpan Pinjam Koperasi Berbasis Website Menggunakan Metode Waterfall - Dede Handayani; Miftakhus Salam (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
KSPPS BMT Al-Bayan is a cooperative for savings and sharia-based financing that is based on the principles of people's economy, independence, and self-sufficiency, as well as being professionally managed with sharia principles. The BMT Al-Bayan cooperative has problems in the transaction data management system, where records are still being done conventionally by writing transaction data on paper by field officers and then handed over to the administration department to be inputted into the Microsoft Access application. As a result, it cannot be easily managed and the process of recording transaction data is repeated. In addition, there is no database-based application, which raises concerns about the ease of damage or loss of transaction data recorded by field officers before being handed over to the administration department. Based on these problems, research was conducted to create an information system application. The research methodology used was interviews, observations, and literature studies. Meanwhile, the system creation methodology used the System Development Life Cycle method with a waterfall model and Unified Modelling Language (UML) as a system depiction. This information system was created using the JavaScript programming language and the Express JS framework as the backend application, the React JS framework for data visualization, and PostgreSQL as the database management system. The result of this research is an information system application that can manage transaction data and customer data, which is expected to help the cooperative authority in managing transaction and customer data